THE REACTION OF INDONESIAN CAPITAL MARKET TO THE RUSSIAN INVASION ON UKRAINE (EVENT STUDY ON COMPANIES LISTED IN THE FOOD AND BEVERAGE SECTOR OF THE INDONESIA STOCK EXCHANGE) - Fian Pakederan; Maryam Mangantar; Lawren J. Rumokoy (Universitas Sam Ratulangi, 2023)
The capital market is an important entity due to its role as an economic indicator for a country. The more important the existence of the capital market is to a country's economy, the more sensitive the market is to available information. This makes an event or incident capable of causing a market reaction, especially if the event can affect the economy and global conditions. On February 24, 2022, the Russian Federation invaded Ukraine, causing a surge in world food commodity prices, especialy wheat. The purpose of this research is to determine the Indonesian capital market's reaction to the Russian invasion of Ukraine, measured by abnormal return, trading volume activity, and market capitalization differences before and after the event. The observation period was conducted for 30 days before and after the event. This study is quantitative and uses comparative methods. The sampling method used is purposive sampling, which gives a research sample of 47 companies in the food and beverage sub-sector of the Indonesian Stock Exchange. The results of this study show that the Russian invasion of Ukraine did not contain information that caused the market to react, as evidenced by the lack of significant differences in abnormal return and market capitalization before and after the invasion. However, the Russian invasion of Ukraine contained information that caused market participants to react in stock trading, as evidenced by significant differences in the trading volume activity variable. Keywords: event study, abnormal return, trading volume activity, market capitalization